ANALISIS SEMIOTIKA: TARADUF KATA GHADAB DAN GHAIZA DALAM AL-QUR’AN - Maryam Nur Annisa (LP2M IAIM Sinjai, 2022)
This article deals with syntax in the qur 'an, which then takes on a semiotical approach. The study was intended to explore the differences in meaning that existed in taraduf, the common meaning of ghadab and ghaiza (mutaradif). However, there was a difference in meaning between the analyzed ghadab and ghaiza using a semiotic approach. The study uses library research's qualitative method of research, analyzing content to arrive at a conclusion. The study suggests that ghadab is mentioned 23 times in 13 different forms, while ghaiza is mentioned 11 times in 9 different forms. Based on this, researchers found a difference in meaning between ghadab and ghaiza. In view of its meaning, the word ghadab is oriented toward anger in a person and is very difficult to undo, in that it is rooted in one's heart. Where as ghaiza in a sense, it is a cause or reason that triggers anger which also comes from the heart. So when challenged, then ghaiza is a level of anger higher than ghadab.